Management of a Critically Ill Post-Cesarean Section Patient with Antepartum Hemorrhage Due to Placenta Previa Totalis in a G2P1A0 at 27–28 Weeks Gestation with Severe Preeclampsia, HELLP Syndrome, Pulmonary Edema, Stage 2 Acute Kidney Injury, and Hypoalbuminemia - Bernadeth, Bernadeth; Erlangga, Muchammad Erias (Journal of Society Medicine, 2025)
Introduction: Massive antepartum hemorrhage in pregnancy, particularly due to placenta previa totalis, poses life-threatening risks requiring intensive care unit (ICU) management. The ROSE (Resuscitation, Optimization, Stabilization, Evacuation) approach is critical in managing critically ill patients with massive bleeding, emphasizing fluid resuscitation, massive transfusion protocols, and coagulopathy management. This case report highlights the complex management of a patient with placenta previa totalis, severe preeclampsia, and HELLP syndrome, complicated by pulmonary edema, acute kidney injury (AKI), and hypoalbuminemia. Case Description: A 35-year-old woman, G2P1A0 at 27–28 weeks gestation, was admitted to the ICU following an emergency cesarean section due to antepartum hemorrhage from placenta previa totalis. She presented with hemorrhagic shock and severe preeclampsia complicated by HELLP syndrome. Initial resuscitation at a referring facility included 2000 cc Ringer’s lactate and 500 cc 0.9% NaCl. In the hospital, damage control surgery and massive transfusion (packed red blood cells, fresh frozen plasma, and platelets) were performed. Postoperatively, the patient required mechanical ventilation and vasopressor support in the ICU. On day 1, she developed volume overload, pulmonary edema, stage 2 AKI, and hypoalbuminemia, managed with furosemide. Extubation was achieved on day 3, and she was transferred to the high-care unit on day 4. Conclusion: In pregnant patients with trauma and massive hemorrhage, early diagnosis, damage control surgery, and appropriate massive transfusion management are critical interventions required to save the patient's life.